2021
DOI: 10.1007/s11302-021-09834-2
|View full text |Cite
|
Sign up to set email alerts
|

P2X7 receptor: the regulator of glioma tumor development and survival

Abstract: P2X7 is an ionotropic nucleotide receptor, forming the cation channel upon ATP stimulation. It can also function as a large membrane pore as well as transmit ATP-dependent signal without forming a channel at all. P2X7 activity in somatic cells is well-known, but remains poorly studied in glioma tumors. The current paper presents the comprehensive study of P2X7 activity in C6 and glioma cell line showing the wide range of effects the receptor has on glioma biology. We observed that P2X7 stimulation boosts gliom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 85 publications
1
3
0
Order By: Relevance
“…Collectively, this supports a role for P2X7 in glioma development as indicated for human P2X7 (Bergamin, et al, 2019, Kan, et al, 2020, Matyśniak, et al, 2022. However, reduced P2X7 activity is typically associated with reduced glioma progression, so it remains unclear how the potential partial J o u r n a l P r e -p r o o f loss-of-function mutation F103L promotes glioma development in dogs.…”
Section: Polymorphic Variants Of Canine P2x Receptorssupporting
confidence: 55%
“…Collectively, this supports a role for P2X7 in glioma development as indicated for human P2X7 (Bergamin, et al, 2019, Kan, et al, 2020, Matyśniak, et al, 2022. However, reduced P2X7 activity is typically associated with reduced glioma progression, so it remains unclear how the potential partial J o u r n a l P r e -p r o o f loss-of-function mutation F103L promotes glioma development in dogs.…”
Section: Polymorphic Variants Of Canine P2x Receptorssupporting
confidence: 55%
“…P2X7R has been shown to increase cellular lactate output and glycogen storage, as well as upregulate glycolytic enzymes, enhancing the ability of tumour cells to adapt to unfavourable ambient conditions 58 . Enhanced mitochondrial depolarisation has also been observed in C6 glioma cells following P2X7R activation 59 . There seems to be a clear metabolic association with P2X7R stimulation.…”
Section: Discussionmentioning
confidence: 89%
“…Within the P2XR subclass, the P2X 7 R subtype is perhaps the most well studied in regard to cancer pathogenesis ( Di Virgilio et al, 2021 ; Hreich et al, 2021 ; Matyśniak et al, 2021 ). Regarding proliferation, it has been shown that the P2X 7 R subtype initiates an intracellular phosphorylation cascade resulting in the activation of the PI3K/Akt and ERK1/2 pathways, key regulators of cancer survival ( Amoroso et al, 2015 ; Salahuddin et al, 2021 ).…”
Section: Purinoreceptorsmentioning
confidence: 99%